Hétérogénéité, tensions implicites et influences sur les formats de travail proposés aux élèves dans l’enseignement/apprentissage de la langue première à l’école - Catherine Delarue-Breton (Recherches en Éducation)
The relationship between educational research and the working formats as proposed to the pupils within the class is, as regards the teaching/learning of the first language, rather opaque. Occupying an intermediate position between didactics and school working formats, the teaching practices, confronted within the class with a heterogeneous and unstable reality, but also often liable to prescriptions which present little homogeneity, add a central dimension to the complexity of the analysis. We suggest here evoking some of the recurring phenomena susceptible to embody the educational practice, and, consequently, to impact the working formats proposed to the pupils. These come within the scope of a certain heterogeneity or of tensions which risk, because they are applied without the actors being aware of them, to damage the coherence of their interventions; they are thus situated, while being not totally foreign to them, below explicit quarrels which sometimes give rise in the social sphere to debates. They act in a more subterranean, but no less powerful way. Some of them are inherent to the taught object, the first language; others are rather connected to the specificity of the educational relation, and concern in particular the implementation of the devices of learning.